2006
DOI: 10.1021/jp063150q
|View full text |Cite
|
Sign up to set email alerts
|

High-Pressure Vibrational Spectroscopy of Energetic Materials:  Hexahydro-1,3,5-trinitro-1,3,5-triazine

Abstract: Vibrational spectroscopy has been used to investigate the room-temperature high-pressure phases of the energetic material hexahydro-1,3,5-trinitro-1,3,5-triazine (RDX). The pressure-induced alterations in the spectral profiles were studied in a compression sequence to 30.2 GPa using Raman spectroscopy and to 26.6 GPa using far-infrared spectroscopy. At pressures near 4.0 GPa, several changes become immediately apparent in the Raman spectrum, such as large frequency shifts, mode splittings, and intensity change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
91
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(94 citation statements)
references
References 22 publications
3
91
0
Order By: Relevance
“…The blue shift observed for external modes is to be expected since the strength of the interactions between the adjacent molecules should increase with the reduction of intermolecular distances. [41][42][43][44] At the same time, the intensity of the mode at 152 cm -1 reduced significantly with the increase of pressure. Furthermore, an abrupt change in the spectrum shape, which can be visualized as evidence for the pressureinduced phase transition, was observed at about 4.4 GPa.…”
Section: Resultsmentioning
confidence: 99%
“…The blue shift observed for external modes is to be expected since the strength of the interactions between the adjacent molecules should increase with the reduction of intermolecular distances. [41][42][43][44] At the same time, the intensity of the mode at 152 cm -1 reduced significantly with the increase of pressure. Furthermore, an abrupt change in the spectrum shape, which can be visualized as evidence for the pressureinduced phase transition, was observed at about 4.4 GPa.…”
Section: Resultsmentioning
confidence: 99%
“…2 The hydrostatic equation of state ͑EOS͒ of RDX at room temperature was obtained by Olinger et al 3 and Yoo et al 4 Both experiments 3,4 found a phase transition from ␣-RDX to ␥-RDX near 4 GPa. Subsequently, Raman spectroscopy has been employed for a detailed investigation of RDX at pressures up to about 4 GPa by Ciezak et al 6 and Dreger and Gupta, 7 who found features in the spectra that are associated with the phase transition at this pressure. Very recently, the structure of the ␥ polymorph has been reported by Davidson et al 8 using a combination of x-ray and neutron diffraction.…”
Section: 5mentioning
confidence: 99%
“…In the solid-state, RDX exists in five polymorphic phases, termed a [1,2], b [3,4], c [5][6][7][8], d [9] and e [10]. Previous works have established a phase as the st form at room temperature, where the six-membered ring RDX molecules posses essentially C s symmetry with two of the NO 2 groups axial and the third equatorial with respect to the triazine ring [11,12].…”
Section: Introductionmentioning
confidence: 99%